PENGARUH PENDEKATAN LOK-R TERHADAP KESADARAN BERPIKIR SISWA DALAM PERSPEKTIF PAULO FREIRE - Syafiq, Irfan Baharudin; Sari, Lintang Meutia; AJ, Binti Lathifaturrohmah; Muzayanah, Muzayanah; Sukamto, Yuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education as one of the state's efforts in educating the nation's life is one of the most important aspects in improving the quality of human resources, especially in Indonesia. Today's 21st century learning integrates many aspects of technology and provides learning according to students' talents and interests and has a significant impact on student knowledge. This study aims to determine whether there is an influence of the LOK-R approach on students' thinking awareness in Paulo Fraire's perspective. The research method used was quantitative research with a sample of 56 students from SMP Negeri 1 Nganjuk which was divided into two classes. This sample is determined by purposive sampling technique which has almost similar criteria. For data analysis, the Independent Sample T Test is used. The results of the research that have been carried out show that there is a positive and significant influence of the LOK-R approach on students' thinking awareness in Paulo Fraire's perspective, with a t-count value of 3,286 > t-table 2,048 which shows that the t-count value exceeds the t-table. It can be concluded that students' thinking awareness can be trained using the LOK-R approach which can facilitate students' learning needs with Literacy, Orientation, Collaboration and Reflection.